The music of the primes : searching to solve the greatest mystery in mathematics - Du Sautoy, Marcus (New York : HarperCollins, 2003)
Explains German mathematician Bernard Riemann's theory about the origins and patterns of prime numbers.
Includes bibliographical references (p. [317]-321) and index.
Booklist starred.
Kirkus Review.
New York Times.
Adult
Keywords: Numbers, Prime; Numbers